Barriers and facilitators of physical activity participation in adults living with type 1 diabetes: A systematic scoping review - Brennan, Marian; Brown, Janie; Ntoumanis, Nikos; Leslie, Gavin (CANADIAN SCIENCE PUBLISHING, 2021)
To identify and map barriers and facilitators of physical activity (PA) in adults living with type 1 diabetes (T1D) in any care setting or environment. A scoping review was conducted in accordance with the PRISMA-ScR guidelines to address the aim of this review. Exclusion/inclusion criteria were determined a priori. Articles captured in the search were subject to title and abstract screening before full-text articles were assessed for eligibility against the exclusion/inclusion criteria. Included articles underwent critical appraisal before being charted, mapped, and discussed. Forty-six articles were included in the final synthesis. Most commonly, articles reported cross-sectional survey studies (46%), then qualitative designs (17%), and opinion or text (17%). Experimental studies accounted for 13% of included articles. Hypoglycaemia/fear of hypoglycaemia was the most commonly reported barrier and patient education the most commonly discussed facilitator. Quality appraisal revealed methodological issues among included articles. Higher quality research with theoretically sound behaviour-change interventions combined with targeted patient education is needed to address hypoglycaemia/fear of hypoglycaemia as a barrier to PA. Novelty: Hypoglycaemia and fear of hypoglycaemia were the most commonly reported barriers to PA in adults with T1D. Powered randomised controlled trials are required to establish efficacy of behaviour change interventions targeting these barriers to PA.